Aplikasi Sistem Manajemen Aset Laboratorium Komputer Pada SMKN2 Kab.Tangerang Menggunakan Framework Laravel8 - Fifit Alfiah; Fuad Muhammad Nur; Dedi Gunawan (UNIVERSITAS RAHARJA, 2022)
A computer laboratory with appropriate instruments is a crucial entity at the SMA and SMK levels because the laboratory is a facility and infrastructure that can provide tools thatare difficult to present in the classroom. So is the case with SMKN 2 Tangerang Regency. But in fact, the conventional computer laboratory asset management and the absence of a system to record room loan histories pose an obstacle for schools to obtain fast and detailed data. This research is intended to produce a web-based asset management application system model that can overcome the problems encountered. This study uses observation, interviews, and literature studies to collect relevant data for further analysis using the PIECES method for the system design and development process. The system is designed with UML and Laravel framework. Extreme Programming is used as an approach to develop the system. The conclusion of this study resulted in a web-based asset management application system that can quickly and detailedly present asset data and computer laboratory room loan history and the use of Laravel provides convenience in building and developing future applications for developers.